(D)-Serine reflects kidney function and diseases - Hesaka, Atsushi (Sci Rep, 2019)
(D)-Amino acids, long-term undetected enantiomers of (L)-amino acids, are now emerging as potential biomarkers, especially for kidney diseases. Management of chronic kidney disease (CKD), a global problem with its high prevalence and poor prognosis, is currently unsatisfactory due to the difficulty in estimating kidney function and in early detection of diseases. We now show that intra-body dynamics of (D)-serine reflect kidney function and diseases. The blood level of (D)-serine correlated well with the actual glomerular filtration ratio, a key kidney function. This correlation was compatible with those of conventional kidney markers, and blood level of (D)-serine was relatively unaffected by such clinical factors as body size. The balance between excretion and reabsorption of amino acids by the kidney was controlled with chiral selectivity, and the reabsorption of (D)-serine was sensitive to the presence of CKD. The combination of blood level and urinary dynamics of (D)-serine effectively distinguished CKD from non-CKD. These lines of evidence provide new insights into the enantioselective amino acid dynamics in the human body that reflect disease pathophysiology. (D)-Serine may serve as a vital biomarker that suppress CKD onset through the precise assessment of kidney function and the diagnosis of CKD.